2016
DOI: 10.1016/j.ijid.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Sexually acquired hepatitis C virus infection: a review

Abstract: Sexually acquired hepatitis C virus (HCV) infection remains a public health problem, with significant disease burden primarily in HIV-positive men who have sex with men (MSM). Over the past decades, the epidemic of sexually transmitted HCV infection has continued to expand and the epidemiology of HCV in HIV has changed significantly. In the post-combination antiretroviral therapy era, sexual network characteristics within the specific core group of MSM with increased sexual risk behaviours, including serosorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 153 publications
(260 reference statements)
3
102
1
7
Order By: Relevance
“…Because use of allografts from HCV‐viremic donors in HCV‐negative recipients is a recent development in transplant medicine, there are no data on possible long‐term hepatic and extrahepatic adverse effects associated with HCV exposure, even among those cured of the infection. Allograft recipients who are HCV viremic can potentially sexually transmit the virus to their partner(s), particularly among MSM …”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
“…Because use of allografts from HCV‐viremic donors in HCV‐negative recipients is a recent development in transplant medicine, there are no data on possible long‐term hepatic and extrahepatic adverse effects associated with HCV exposure, even among those cured of the infection. Allograft recipients who are HCV viremic can potentially sexually transmit the virus to their partner(s), particularly among MSM …”
Section: Organ Transplantation From Hcv‐viremic Donors To Hcv‐negativmentioning
confidence: 99%
“…Globally, approximately 25% of cases of cirrhosis and HCC are attributed to HCV 4. HCV primarily is a bloodborne pathogen but the increasing number of HIV-positive MSM with acute HCV diagnosed in the early 2000s suggested that its epidemiology was changing 5. Using a phylogenetic approach, the independently reported HCV outbreaks in various large cities across Europe proved to be part of one large international MSM-specific HCV transmission network 6.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-negative MSM with sexually acquired HCV often report HIV-positive sexual partners,15 29 31 continuous introductions of HCV among the population without HIV might eventually result in an expanding HCV epidemic irrespective of HIV status. The increased popularity of Internet, mobile phone geosocial networking applications, MSM tourism and circuit (sex) parties may have provided an ideal platform for high-risk HIV-positive and HIV-negative MSM to extend their sexual networks 5 32. The formation of highly interconnected high-risk sexual networks may partly explain the successful expansion and rapid international dissemination of newly introduced STIs in recent years 6…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the transmission rates of HCV as a STI is very low among heterosexual couples. Similarly, the rate of sexually transmited HCV infection in HIV-negative MSM is low [40].…”
Section: Risk Factors For Stismentioning
confidence: 99%
“…Some behaviors including having multiple sex partners, sexual intercourse without condom use, illicit drug use, sharing of injected equipment's, and alcohol use are generally associated with a higher prevalence of HIV/STIs [5]. High-risk behaviors such as serosorting and chemsex may increase the rate of sexually transmited HCV [40].…”
Section: Risk Factors For Stismentioning
confidence: 99%